Cardiac sub-volume targeting demonstrates regional radiosensitivity in the mouse heart. (November 2020) - Ghita, Mihaela; Gill, Eleanor K.; Walls, Gerard M.; Edgar, Kevin S.; McMahon, Stephen J.; Osorio, Eliana Vasquez; Bergom, Carmen; Grieve, David J.; Watson, Chris J.; McWilliam, Alan; Aznar, Marianne; van Herk, Marcel; et al.
Highlights: First preclinical model showing the base of the heart as a radiosensitive sub-volume. C57BL/6 mice were irradiated at the base, middle or apex of the heart. Base irradiated mice showed the most significant decreases in cardiac function. The observed functional changes did not correlate with MHD and V5. Abstract: Background and purpose: Radiation-induced cardiac toxicity (RICT) remains one of the most critical dose limiting constraints in radiotherapy. Recent studies have shown higher doses to the base of the heart are associated with worse overall survival in lung cancer patients receiving radiotherapy. This work aimed to investigate the impact of sub-volume heart irradiation in a mouse model using small animal image-guided radiotherapy. Materials and methods: C57BL/6 mice were irradiated with a single fraction of 16 Gy to the base, middle or apex of the heart using a small animal radiotherapy research platform. Cone beam CT and echocardiography were performed at baseline and at 10 week intervals until 50 weeks post-treatment. Structural and functional parameters were correlated with mean heart dose (MHD) and volume of heart receiving 5 Gy (V5). Results: All irradiated mice showed a time dependent increase in left ventricle wall thickness in diastole of 0.2 mm detected at 10 weeks post-treatment, with the most significant and persistent changes occurring in the heart base-irradiated animals. Similarly, statistically different functional effects ( p < 0.01) were observed in base-irradiated animals which showed the most significant decreases compared to controls. The observed functional changes did not correlate with MHD and V5 ( R 2 < 0.1), indicating that whole heart dosimetry parameters do not predict physiological changes resulting from cardiac sub-volume irradiation. Conclusions: This is the first report demonstrating the structural and functional consequences of sub-volume targeting in the mouse heart and reverse translates clinical observations indicating the heart base as a critical radiosensitive region.